2016
DOI: 10.1038/ncomms12845
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative genomics reveals adaptive evolution of Asian tapeworm in switching to a new intermediate host

Abstract: Taenia saginata, Taenia solium and Taenia asiatica (beef, pork and Asian tapeworms, respectively) are parasitic flatworms of major public health and food safety importance. Among them, T. asiatica is a newly recognized species that split from T. saginata via an intermediate host switch ∼1.14 Myr ago. Here we report the 169- and 168-Mb draft genomes of T. saginata and T. asiatica. Comparative analysis reveals that high rates of gene duplications and functional diversifications might have partially driven the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 69 publications
7
36
0
Order By: Relevance
“…However, the present analysis based on the L-shaped Ks age distribution revealed that paleopolyploidies are probably absent in the fluke lineage in a relatively long evolutionary time (Ks ≤ 5) (Figure 1 ). It is consistent with the case of the investigation of paralogous genes in tapeworms that no sudden peak was observed in Ks age distributions (Wang et al, 2016 ). This estimation is further confirmed by the result from the collinearity block analysis that no genomic region with more than 5 genes was successfully called by MCScanX algorithm, indicative of absence of large segmental duplications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the present analysis based on the L-shaped Ks age distribution revealed that paleopolyploidies are probably absent in the fluke lineage in a relatively long evolutionary time (Ks ≤ 5) (Figure 1 ). It is consistent with the case of the investigation of paralogous genes in tapeworms that no sudden peak was observed in Ks age distributions (Wang et al, 2016 ). This estimation is further confirmed by the result from the collinearity block analysis that no genomic region with more than 5 genes was successfully called by MCScanX algorithm, indicative of absence of large segmental duplications.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, some duplicated genes have been demonstrated to play central roles in adaptations to some specific niches, such as, Dca gene that is involved in adaptation to lower temperature in Drosophila (Arboleda-Bustos and Segarra, 2011 ), and major histocompatibility complex (Burri et al, 2010 ) and immunoglobulin gene families (Guldner et al, 2004 ) that are likely linked to host-pathogen interactions. For an evolutionarily specialized group, parasites have undergone long-term adaptations and evolved a lot of specialized mechanisms to interact with their hosts during life cycles (Tsai et al, 2013 ; Jackson, 2015 ; Zarowiecki and Berriman, 2015 ; Wang et al, 2016 ). Therefore, it will be particularly important to investigate the nature and extent of GD in genomes of parasites to better understand the associations between GD events and evolutionary adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Novel genes and duplications are thought to be primary forces in species-specific adaptation and divergence by allowing the differentiation of gene functions 10,11 . Thus, they may provide insights into the understanding of fall webworm-specific attributes.…”
Section: Specific Genes and Gene Family Expansions In The Fall Webwormmentioning
confidence: 99%
“…Arbitrarily, proteins were selected from each taxon by considering identity and expected values. Two orthologous proteins that found in Taenia saginata by blast search in WormBase ParaSite ( http://parasite.wormbase.org/Multi/Tools/Blast?db=core ) were also included [ 27 ]. Amino acid sequences of selected proteins were aligned with ClustalW and applied in a phylogenetic analysis using the maximum-likelihood algorithm of Mega 6.0 ( http://www.megasoftware.net/ ) (Jones-Thornton-Tayler model for amino acid substitution, rate heterogeneity with 4 gamma category).…”
Section: Methodsmentioning
confidence: 99%